Coexistence of OSA may compensate for sleep related reduction in neural respiratory drive in patients with COPD. Issue 3 (2nd November 2016) - He, Bai-Ting; Lu, Gan; Xiao, Si-Chang; Chen, Rui; Steier, Joerg; Moxham, John; Polkey, Michael I; Luo, Yuan-Ming
Abstract : Background: The mechanisms underlying sleep-related hypoventilation in patients with coexisting COPD and obstructive sleep apnoea (OSA), an overlap syndrome, are incompletely understood. We compared neural respiratory drive expressed as diaphragm electromyogram (EMGdi ) and ventilation during stage 2 sleep in patients with COPD alone and patients with overlap syndrome. Methods: EMGdi and airflow were recorded during full polysomnography in 14 healthy subjects, 14 patients with OSA and 39 consecutive patients with COPD. The ratio of tidal volume to EMGdi was measured to indirectly assess upper airway resistance. Results: Thirty-five patients with COPD, 12 healthy subjects and 14 patients with OSA completed the study. Of 35 patients with COPD, 19 had COPD alone (FEV1 38.5%±16.3%) whereas 16 had an overlap syndrome (FEV1 47.5±16.2%, AHI 20.5±14.1 events/hour). Ventilation (VE ) was lower during stage 2 sleep than wakefulness in both patients with COPD alone (8.6±2.0 to 6.5±1.5 L/min, p<0.001) and those with overlap syndrome (8.3±2.0 to 6.1±1.8 L/min). Neural respiratory drive from wakefulness to sleep decreased significantly for patients with COPD alone (29.5±13.3% to 23.0±8.9% of maximal, p<0.01) but it changed little in those with overlap syndrome. The ratio of tidal volume to EMGdi was unchanged from wakefulness to sleep in patients with COPD alone and healthy subjects but was significantly reduced in patients with OSA or overlap syndrome (p<0.05). Conclusions: Stage 2 sleep-related hypoventilation in COPD alone is due to reduction of neural respiratory drive, but in overlap syndrome it is due to increased upper airway resistance.